S1-guideline sebaceous carcinoma: guideline - Utikal, Jochen; Nagel, Pia; Müller, Verena; Becker, Jürgen C.; Dippel, Edgar; Frisman, Alexander; Gschnell, Martin; Griewank, Klaus; Hadaschik, Eva; Helbig, Doris; Hillen, Uwe; Leiter, Ulrike; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
Sebaceous gland carcinomas are rare malignant cutaneous adnexal tumors with sebocytic differentiation. The typical predilection area is the head and neck region, where sebaceous gland carcinomas are the most common malignant adnexal tumors of the skin. According to their localization a distinction is made between periocular and extraocular sebaceous gland carcinomas. Muir-Torre syndrome (MTS) should always be ruled out if it is suspected. In terms of prognosis, sebaceous gland carcinomas are potentially aggressive tumors with a clear tendency to recur and metastasize. Only small extraocular sebaceous gland carcinomas that have been completely resected have a very good prognosis. Sebaceous gland carcinomas most frequently metastasize lymphogenously to regional or distant lymph nodes; organ metastasis occurs less frequently. Periocular sebaceous gland carcinomas have a higher metastasis rate (up to 15%) than extraocular sebaceous gland carcinomas (up to 2%). Complete micrographically controlled surgery (MCS) of the primary tumor is the therapy of first choice, regardless of periocular or extraocular localization. Adjuvant or therapeutic radiotherapy may be considered. There is currently no established standard therapy for advanced, inoperable, or metastatic sebaceous gland carcinomas. Local procedures and systemic therapies such as chemotherapy or immunotherapy can be considered. The procedure should be determined individually by an interdisciplinary tumor board. Close follow-up care is recommended for these potentially aggressive carcinomas.
Erstmals veröffentlicht: 28. April 2024
Gesehen am 29.10.2024